National Referendum as an Example for Legitimizing Authoritarian Rule (the Case of the Republic of Belarus after 1991) - Ziętara, Wojciech (What’s New in the New Europe? Redefining Culture, Politics, Identity, 2019)
The article is the result of research project no. 2014/15/B/HS5/01866 funded by the National Science Centre.